Proses dan Dampak Pembelajaran Menulis Teks Anekdot melalui Problem Based Learning Berbantuan Media Dart Board - Fahman Nur Faizi; Titin Nurhayatin; Irfan Rifai (Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study explores the implementation of Problem-Based Learning (PBL) supported by Dart Board media in teaching anecdotal text writing to develop students’ creative thinking skills. The research aims to describe both the instructional process and the impact of PBL with Dart Board media on students’ anecdotal writing. A qualitative research design was employed, involving classroom observations, interviews, and document analysis conducted in one senior high school in Padalarang. The participants consisted of 31 students. Data were analyzed through data reduction, display, verification, and cyclical coding across two instructional cycles. The findings indicate that the application of PBL assisted by Dart Board media positively influenced the learning process, as reflected in increased student participation, greater diversity of ideas, and improved originality in students’ anecdotal texts. However, the study also identified challenges, particularly the extended instructional time required for effective implementation. These findings suggest that while PBL integrated with interactive media has strong potential to enhance creative writing skills, careful consideration of time management and classroom space is essential to maximize its effectiveness. Overall, this study supports the use of interactive and problem-based instructional strategies to foster creativity in writing instruction